2013
DOI: 10.1371/journal.pone.0082308
|View full text |Cite
|
Sign up to set email alerts
|

Mir-29 Repression in Bladder Outlet Obstruction Contributes to Matrix Remodeling and Altered Stiffness

Abstract: Recent work has uncovered a role of the microRNA (miRNA) miR-29 in remodeling of the extracellular matrix. Partial bladder outlet obstruction is a prevalent condition in older men with prostate enlargement that leads to matrix synthesis in the lower urinary tract and increases bladder stiffness. Here we tested the hypothesis that miR-29 is repressed in the bladder in outlet obstruction and that this has an impact on protein synthesis and matrix remodeling leading to increased bladder stiffness. c-Myc, NF-κB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 48 publications
(86 reference statements)
2
82
0
3
Order By: Relevance
“…We identified JUND, BDNF, and CCND1 among hubs of signaling activity targeted by miR-1 in human BOO patients. A recent expression profile in a rat pBOO model showed a decrease of miR-29b and miR29c concomitant with an upregulation of c-Myc, NFkB, and SMAD3 (16). Our results confirm these findings in human patients with BOO.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We identified JUND, BDNF, and CCND1 among hubs of signaling activity targeted by miR-1 in human BOO patients. A recent expression profile in a rat pBOO model showed a decrease of miR-29b and miR29c concomitant with an upregulation of c-Myc, NFkB, and SMAD3 (16). Our results confirm these findings in human patients with BOO.…”
Section: Discussionsupporting
confidence: 88%
“…Reliable markers of bladder function are urgently needed in order not to surpass the "point of no return," leading to bladder decompensation and failure. The studies of individual cellular signaling pathways conducted in animal models (5-7) identified some of the regulated genes typical for a specific symptomatic state; similarly, a number of regulatory miRNAs have been implicated in bladder pathologies (8)(9)(10)(11)(12) and function (13). Increasing evidence indicates that miRNAs may play a role in the regulation of urothelial permeability (14) and bladder contractility (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…We reported 1) increased matrix area between smooth muscle cells, 2) reduced depolarization-induced contraction, and 3) a pronounced impairment of the cholinergic component of neurogenic bladder activation. We have subsequently attributed the increased matrix area in the dicer KO bladder to miR-29 (14), which targets multiple extracellular matrix proteins, but the miRNAs responsible for the reduction of depolarization-induced contraction and impaired neurogenic activation have not been identified. We show here that depolarization-induced contraction and neurogenic activation is maintained in miR-143/145 KO bladders, arguing that miRNAs other than miR-143/145 must be responsible for reduced depolarization-induced contraction and neurogenic activation in dicer KO bladders.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first time to report bladder-neck fibrosis associated with BOO. The bladder-body detrusor fibrosis has been reported in rodents with surgical obstruction of urethra, [36][37][38] aromatase-overexpressing mice 6 and T þ E2-treated mice. 12 The abnormal deposition of collagen in the bladder neck and body, as a consequence of urinary obstruction, may further increase the stiffness and matrix rigidity of LUT leading to the decompensated stage of BOO.…”
Section: Wtmentioning
confidence: 99%